Transient Increase in Cellular Dehydrogenase Activity After Cadmium Treatment Precedes Enhanced Production of Reactive Oxygen Species in Human Proximal Tubular Kidney Cells - Handl, Jiří; Čapek, Jan; Majtnerová, Pavlína; Petira, Filip; Hauschke, Martina; Roušarová, Erika; Roušar, Tomáš (Czech Academy of Sciences, Institute of Physiology, 2019)
Cadmium is a heavy metal causing toxicity especially in kidney cells. The toxicity is linked also with enhanced oxidative stress leading to cell death. On the other hand, our recent experiments have shown that an increase of total intracellular dehydrogenases activity can also occur in kidney cells before declining until cell death. The aim of the present study, therefore, was to evaluate this transient enhancement in cell viability after cadmium treatment. The human kidney HK-2 cell line was treated with CdCl2 at concentrations 0-200 μM for 2-24 h and intracellular dehydrogenase activity was tested. In addition, we measured reactive oxygen species (ROS) production, glutathione levels, mitochondrial membrane potential, and C-Jun-N-terminal kinase (JNK) activation. We found that significantly increased dehydrogenase activity could occur in cells treated with 25, 100, and 200 μM CdCl2. Moreover, the results showed an increase in ROS production linked with JNK activation following the enhancement of dehydrogenase activity. Other tests detected no relationship with the increased in intracellular dehydrogenase activity. Hence, the transient increase in dehydrogenase activity in HK-2 cells preceded the enhancement of ROS production and our finding provides new evidence in cadmium kidney toxicity.
Přechodné zvýšení dehydrogenázové aktivity buněk ovlivněných kadmiem předchází zvýšené produkci reaktivních forem kyslíku u lidských proximálních tubulárních buněk ledvin
Keywords: cadmium toxicity; kidney injury; dehydrogenase activity; oxidative stress; ROS production; toxicita kadmia; poškození ledvin; dehydrogenázová aktivita; oxidační stres; produkce ROS